Wedged gel pad for bowel manipulation during MR-guided high-intensity focused ultrasound therapy to treat uterine fibroids: a case report - Teija Sainio; Gaber Komar; Jani Saunavaara; Visa Suomi; Kirsi Joronen; Antti Perheentupa; Antti Viitala; Roberto Blanco Sequeiros (BMC, 2022)
Magnetic resonance guided high-intensity focused ultrasound (MR-HIFU) therapy is not feasible in all patients with uterine fibroids because of limiting anatomical factors such as scar tissue, bowel loops or other obstacles in the sonication path. These may prevent the treatment or limit the treatment window, and therefore, also the volume where HIFU therapy can be delivered. Bowel loops present a particular problem because of bowel gas bubbles and hard particles which may cause reflection or absorption of ultrasound energy, potentially leading to thermal damage and even bowel perforation. Most commonly used techniques for bowel repositioning are bladder and/or rectum filling but these are not always sufficient to reposition the bowel loops. With more efficient bowel repositioning technique, the number of eligible patients for MR-HIFU treatment could be increased, and therapy efficacy be improved in cases where bowel loops limit the treatment window.
A wedged exterior gel pad was used in two patients presented with in total of four symptomatic fibroids undergoing MR-HIFU treatment when bladder and/or rectum filling was not sufficient to reposition the bowel loops. No severe adverse effects were observed in these cases. The non-perfused volume ratios (NPVs) immediately after treatment were 86% and 39% for the first patient, and 3% for the second patient.
Our preliminary experience suggests that the use of a wedged gel pad during MR-HIFU treatment could be an effective tool to manipulate the bowels in cases where the bladder and/or rectum filling is not sufficient to reposition the bowel loops. A wedged gel pad could also be used in other situations to achieve better treatment coverage to the uterine fibroid.